2014
DOI: 10.5539/cco.v3n2p43
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laparosopic Hyperthermic Intraperitoneal Chemotherapy for Peritoneal Metastasis from Gastric Cancer

Abstract: Background: The purpose of this manuscript is to report the direct effects of hyperthermic intraperitoneal chemotherapy (HIPEC) in gastric cancer-patients with peritoneal metastasis (PM). Materials and Methods:Thirty-five patients with PM were enrolled, and were treated with neoadjuvant laparoscopic HIPEC (LHIPEC). LHIPEC was performed at 42 to 43 centigrade for 60 minutes adding 3 liter of saline plus 12.5mg/m2 of Mitomycin C with Cisplatin (50mg/m 2 ). Second session of LHIPEC was done one month after the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Outcome after CRS is reported to significantly correlate with negative peritoneal cytology than with positive peritoneal cytology. 18 Multivariate analysis in the present study also demonstrated the cytologic status after NLHIPEC plus NIPS (but not at NLHIPEC) as an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Outcome after CRS is reported to significantly correlate with negative peritoneal cytology than with positive peritoneal cytology. 18 Multivariate analysis in the present study also demonstrated the cytologic status after NLHIPEC plus NIPS (but not at NLHIPEC) as an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 66%
“…Yonemura et al first reported the direct effect of NLHIPEC with or without NIPS on PCI determined by laparoscopy in 2016, and they found that neoadjuvant chemotherapy reduced PCI below its cut-off level in half of their patients. 18 Coccolini et al reported that PCI cut-off level at laparotomy is an independent prognostic factor after CRS. 19 However, which PCI cut-off (Pre-PCI vs Post-PCI cut-off) relates to prognosis remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that the bidirectional chemotherapy with cisplatin and docetaxel had effects on cytology, ascites status and PCI (7). We have also studied in vivo pharmacokinetics of docetaxel in 11 patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…HIPEC increased the depth of CDDP and carboplatinum penetration up to 3 mm from the peritoneal surface [22], and 40 min. of HIPEC increased the depth of DTX penetration 1.46 mm [36,30,42]. Accordingly, HIPEC is considered to be an effective for PM treatment.…”
Section: Effects and Side Effects Of Hyperthermic Intraperitoneal Chemoperfusion (Hipec)mentioning
confidence: 98%